Rituals and Social Cohesion: Cultural Preservation Through Djawa Sunda Cosmology in Cigugur, Kuningan, Indonesia - Alfan, Muhammad (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This research aims to explore how the Djawa Sunda Religion (Agama Djawa Sunda-ADS) contributes to the preservation of cultural identity and religious practices in the Cigugur community, Kuningan, amidst modernisation and globalisation. Using a qualitative and ethnographic approach, the study focused on documenting the evolution and continued relevance of ADS cosmology through rituals and ceremonies such as Seren Taun. Data collection was conducted through interviews with religious leaders and community members, participant observation, and document analysis. The findings reveal that ADS plays a significant role in maintaining social cohesion and cultural continuity through its cosmological teachings and community rituals despite external pressures of cultural assimilation. The study also highlights the role of ADS in fostering religious pluralism and tolerance in a diverse religious community. The application of this research provides insights for scholars and policymakers interested in cultural preservation and religious pluralism in indigenous communities. The novelty of this study lies in its comprehensive analysis of ADS within the framework of Sundanese cosmology, contributing new perspectives on the intersection of religion, culture, and modernisation in Indonesia.